2021
DOI: 10.15622/ia.20.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Cyberattack detection in vehicles using characteristic functions, artificial neural networks, and visual analysis

Abstract: The connectivity of autonomous vehicles induces new attack surfaces and thusthe demand for sophisticated cybersecurity management. Thus, it is important to ensure thatin-vehicle network monitoring includes the ability to accurately detect intrusive behavior andanalyze cyberattacks from vehicle data and vehicle logs in a privacy-friendly manner. For thispurpose, we describe and evaluate a method that utilizes characteristic functions and compareit with an approach based on artificial neural networks. Visual ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In the future, we plan to expand the experiments on attack detection by simulating other various kinds of attacks targeted at self-organizing decentralized WSNs with the help of the used software/hardware test-bench. It is also planned to test this complex approach to attack detection in the field of autonomous vehicles [36]. Vehicle swarms can be carriers of WSNs and could be used to extend the range of ground-based WSNs, and they can also perform the function of measuring environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we plan to expand the experiments on attack detection by simulating other various kinds of attacks targeted at self-organizing decentralized WSNs with the help of the used software/hardware test-bench. It is also planned to test this complex approach to attack detection in the field of autonomous vehicles [36]. Vehicle swarms can be carriers of WSNs and could be used to extend the range of ground-based WSNs, and they can also perform the function of measuring environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, we considered visualization models as an alternative to graphs as a component of human–machine interaction, inspired by the visualization approaches used in bioinformatics. Despite their low prevalence, it has been shown that they can be an alternative to the established methods of presenting data in various application areas, such as transport systems [ 34 , 98 ], water supply management systems [ 99 ], critical infrastructures [ 100 ], mobile payment systems [ 101 ], social networks [ 102 ], and digital forensics [ 103 ]. The specificity of each model was shown, and the models leveled out the shortcomings in each other.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to graphs, there are many other alternative visualization models that are successfully applied in various fields. Of course, these models are Concerning some application areas where graph data structures are common, for example, for the analysis of social networks, computer networks, transport flows, etc., the adaptation of alternative models from bioinformatics makes it possible to get partially rid of the problems inherent in graphs and can provide researchers with a potential alternative to graph models for analyzing the data in other research areas [34].…”
Section: State Of the Artmentioning
confidence: 99%
“…In [73], a study investigates the use of a context aware IDS for detecting cyberattacks on the CAN bus and use the ROAD dataset for training. The potential of embedding an IDS that utilizes characteristic functions is proposed in [79], where researchers evaluate the cybersecurity framework on ROAD. In [77], researchers utilize the ROAD dataset to validate a model called "Deep Evolving Stream Clustering-IDS" or DESC-IDS.…”
Section: Plos Onementioning
confidence: 99%